Implementation Of Istishna 'Aqd In The Financial Investment Scheme Of Koperasi Syariah Benteng Mikro Indonesia - Komarudin, Muhamad (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to examine the implementation of Istishna ‘aqd in investment financing at Koperasi syariah BMI, Ciawi branch. The issue addressed in this study is that the Istishna ‘aqd, substantively, is not an investment aqd but rather a sales aqd. Therefore, a comprehensive analysis is needed to determine the permissibility of utilizing the Istishna aqd in investment financing or to explore potential changes in the financing model or ‘aqd used. The research employs a qualitative descriptive method with data collection techniques through interviews and secondary data collection from the website, reports, and guidelines of Koperasi Syariah BMI. The study investigates how the Istishna ‘aqd is implemented in investment financing and its compliance with Sharia principles, aiming to conclude the feasibility of applying the Istishna ‘aqd in investment financing at Koperasi Syariah BMI. Based on the research findings, it is observed that the Istishna ‘aqd scheme applied in investment financing at Koperasi Syariah BMI is more aligned with the Fatwa DSN MUI No 06/DSN MUI/IV/2000 on Istishna, which involves a regular Istishna ‘aqd between two consenting parties. This approach deviates from the guidance of Fatwa DSN MUI No 32/DSN-MUI/IX/2002 on Sharia bonds, where Istishna is used in investment schemes, and is also inconsistent with Fatwa DSN MUI No 22/DSN MUI/III/2002 on parallel Istishna, as the cooperative already possesses a company engaged in building material provision. Despite the compliance of Istishna-based financing in Koperasi Syariah BMI with Fatwa DSN MUI No 06/DSN MUI/IV/2000, it is recommended that the cooperative adopt terminologies such as consumptive financing, productive financing, property ownership financing, or other terms in financing schemes involving Istishna ‘aqd. This suggestion is made due to the fact that cooperative members do not function as investors but as buyers seeking financing for development schemes such as housing, sanitation, and the provision of clean water.